A survey on redundancy mechanisms in time-sensitive networking - Zimei PENG; Guochu SHOU; Mengjie GUO; Yaqiong LIU; Yihong HU (Dianxin kexue)
Many network applications, such as industrial control and automatic driving, have high requirements for network reliability.Time-sensitive networking (TSN) is a new generation of network technology based on the evolution of standard Ethernet architecture, including the frame replication and elimination for reliability (FRER).Firstly, the redundancy mechanism in TSN standard was described, including the development process, relevant standards and research status.Secondly, the spatial redundancy and time redundancy mechanisms in TSN were classified and analyzed.Finally, the future development and application scenarios of the redundancy mechanism in TSN were prospected, and some inspiring research directions and ideas were put forward.